Introduction to a Reading of Spinoza - Santiago, Homero (Discurso, 2020)
Over five decades, the Brazilian philosopher Marilena Chaui produced one of the most vigorous and important interpretations of Spinoza’s philosophy. In this paper we intend to propose an introduction to this reading. We would like to show how, at the same time, this interpretation 1) has its initial steps in the wake of Spinoza’s French rediscovery in the 1960s; 2) according to the author’s own report, it was elaborated mainly in the 70’s “under the sign of the criticism of the dictatorship”, and in this reading the history of philosophy was practiced as “critique of that which has been instituted”, or even more precisely, as a comprehensive and critical analysis of Brazilian authoritarianism. Which are the circumstances of this operation? It is what we intend to investigate.